Workplace well-being pada Perawat di Rumah Sakit tinjauan antara Job Demand dan Psychological Capital - Mohamad Lutfi Hakim; Trubus Raharjo (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze and empirically prove the relationship between job demands and psychological capital with Workplace well-being among nurses. This quantitative correlational study involved 236 nurses at a hospital in Kudus Regency, selected through a quota sampling technique. Data collection utilized the Workplace well-being scale, job demands scale, and psychological capital scale instruments. Data analysis was performed using a two-predictor regression analysis method and product-moment correlation. The results showed a highly significant relationship simultaneously between job demands and psychological capital with Workplace well-being ( = 0.556, p < 0.01), yielding an effective contribution of 30.9%. Partially, there was a highly significant negative relationship between job demands and Workplace well-being (r = -0.533, p < 0.01), as well as a highly significant positive relationship between psychological capital and Workplace well-being (r = 0.274, p < 0.01). The study concludes that a decrease in job demands, accompanied by the strengthening of internal psychological capital, is empirically proven to increase nurses' workplace well-being.